Conocimientos y actitudes sobre el vector Aedes aegypti según el nivel socioeconómico en la población de los sectores 26 y 29 de la ciudad de Iquitos, Loreto - Perú - Charpentier Vilchez, Genix Samuel (2023)
The knowledge and attitudes about the Aedes aegypti vector were determined according to the socio-economic level in the population of sector 26 and 29 of the city of Iquitos, Loreto - Peru. During the months of August to November 2021, a descriptive longitudinal study was carried out. Two types of surveys were developed, one on knowledge and attitudes, another to determine the socio-economic level of 362 people, between 16 and 83 years old. 92.7% of the population in sector 26 have a regular level of knowledge about the vector Aedes aegypti and in sector 29 84.7%. Regarding attitudes, both sectors showed good attitudes with 93.9% and 97.7% respectively. The predominant socio-economic level for each sector was C=Medium level (59.4%), The correlation between the socio-economic level and knowledge had a Rho equal to 0.290, however, the correlation between attitudes with the socio-economic level economical had a Rho=0.021. concluding that knowledge in both sectors is regular, attitudes are good and the socioeconomic level that most predominates is the middle level (C). Knowledge has a low direct significant relationship (p>0.05) with the socio-economic level, however, the correlation between attitudes and the socioeconomic level has a high direct significant relationship.